Tindak Tutur Direktif Guru dalam Pembelajaran Bahasa Indonesia Di SMA Negeri 2 Gunung Talang - Yulia Marizal; Sayhrul R.; Tressyalina Tressyalina (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2021)
This study aimed to describe the form of teacher directive speech acts in learning Indonesian at SMA Negeri 2 Gunung Talang. This type of research is qualitative research with a descriptive method. The research data used is the teacher's speech in learning Indonesian at SMA Negeri 2 Gunung Talang. The data source is Mrs. Indra Dewi as an Indonesian teacher at SMA Negeri 2 Gunung Talang. The data collection technique used the free-of-conversation listening technique. Data analysis techniques are listening, understanding, organizing, categorizing, connecting between categories, and interpreting data based on the context. The results of this study contained five forms of directive speech acts, namely requesting speech, wishing speech, commanding speech, welcome speech, and asking speech. The utterance asks to be reviewed from the words "please" and "come on." Speeches of hope are viewed from the word "hope" or "hope." Speech orders are reviewed from the words "try" and "quick." Speech please viewed from the word "please." Asking utterances are viewed from the words "what," "who," and "how."